IMPLEMENTATION OF E-GOVERNMENT THROUGH IMPLEMENTATION OF TECHNOLOGY ACCEPTANCE MODEL - Mayasari, Iin; Hendrowati, Retno; Sofia, Asriana Issa; Wiadi, Iyus (Universitas Brawijaya, Indonesia, 2017)
The objective of the study is to analyze the implementation of e-government of the users. The users were the citizen of Bogor City and the government officers in Bogor Government. The implementation of e-government was related to the website application of Bogor Government. The users were considered as the important thing because they could understand and comprehend the benefit of government website and the effectiveness of egovernment implementation. The focus of the study was the implementation of the theory of technology acceptance model. The concept involved the perceived usefulness, the perceived ease of use, and the subjective norm. The model of TAM was extended by involving the perceived risk to clarify of the acceptance of e-government use. The research method was to collect the data and used the survey for distributing the questionnaires of 414 citizens as the respondents in Bogor City. The research result showed that the perceived use influenced the use of the website but it was not significant; meanwhile the perceived ease of use, the perceived risk and the subjective norm influenced the use of the website significantly.